Temperature-resistant and salt-resistant organic / inorganic composite gel with delayed crosslinking of urea and preparation method of temperature-resistant and salt-resistant organic / inorganic composite gel
Through the method of delaying cross-linking and regulating the precipitation reaction of calcium and magnesium ion, the problem of short glue formation time of composite gel under high temperature conditions is solved, and the long-term stability of composite gel and the application under high temperature and high salt conditions is achieved. It is suitable for Deep oil field dissection and block water.
Patent Information
- Application Number
- CN202411600135.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-02-18
AI Technical Summary
The prior art has a short glue forming time of organic/inorganic composite gel under high temperature conditions, which is difficult to meet the demand for deep dissection and blocking of water in oil fields. At the same time, the compatibility of inorganic particles and high mineralization formation water when preparing composite gels is poor, which limits the Its application.
The method of delaying crosslinking of urea is used to delay crosslinking, and ammonia and carbon dioxide are produced by decomposition of urea, hydroxide and carbonate anions are generated, and the crosslinking reaction between polyacrylamide and phenolic substances is inhibited, and the calcium and magnesium ion precipitation reaction is used to regulate the precipitation reaction of calcium and magnesium ion to form Organic/inorganic composite gels extend gel formation time and improve gel stability.
The gel forming time of composite gel under high temperature and high salt conditions of 95-120℃ has been controlled. The gel forming time can be adjusted from 2.2-26.4 days, and the gel stabilization time exceeds 135 days, which significantly improves the temperature resistance of the gel. Salt resistance and stability, suitable for deep water regulation and blocking in high-temperature and high-salt reservoirs.
Smart Images

Figure CN119463830A_ABST
Abstract
Description
Technical field:
[0001] The invention belongs to the field of new materials for oilfield development, and in particular relates to a heat-resistant and salt-resistant organic / inorganic composite gel with delayed cross-linking of urea and a preparation method thereof. Background technology:
[0002] Oil is a non-renewable resource, and oil production has an important impact on the growing demand for energy and chemical raw materials. At present, the global crude oil recovery rate is only 20-40%, and a large amount of crude oil is retained in the formation and cannot be recovered. This is mainly due to the heterogeneity of the formation. Usually, the fluid flows along the high permeability layer and forms a channel from the injection well to the production well too early. As a result, the water content of the production well output fluid exceeds 95% or even higher. At the same time, the crude oil in the low permeability layer cannot be developed. The above situation increases the cost of output fluid treatment on the one hand, and the crude oil recovery rate is seriously affected. In oil field production, gel liquid is often injected into the injection well to adjust the water absorption profile of the formation, or gel liquid is injected into the production well to plug the high permeability layer. These measures force the subsequent injection of displacement fluid into the low permeability layer, and improve the crude oil recovery rate by increasing the swept volume or oil displacement efficiency. Profile adjustment and water plugging have become an important measure to increase oil field production.
[0003] The gels used in the process of profile control and water plugging usually include inorganic gels, polymer organic gels, and organic / inorganic composite gels. Inorganic gels include silicate or silica gel, aluminosilicate gel, aluminum hydroxide gel, etc. The advantages of these substances are good salt resistance, but the preparation process is easily affected by the reaction temperature and pH value, especially under high temperature conditions, the gelation time of the reaction liquid is short and difficult to control. The literature [Hong He, Yefei Wang, Ziyuan Qi, Xiaojie Sun, Gelation performance and feasibility study of an environmentally friendly improved inorganic aluminum gel for conformance control under harsh reservoir conditions, Journal of Energy Resources Technology, 2017, 139, 012911] studied the gelation performance of aluminum hydroxide. When the reaction temperature increased from 90°C to 130°C, the gelation time of the reaction system decreased from 95h to 3.5h. High-temperature rapid gelation cannot meet the requirements of deep profile control in oil fields. Patent CN108003855A discloses a single-liquid inorganic precipitation plugging agent and its preparation method, that is, using formation water to gradually dilute the anti-scaling agent, and gradually forming calcium carbonate particles in the formation to block the water flow channel. However, the inorganic particles formed in this study can only block low permeability layers, with a blocking rate of 54.9-64.6%, and its applicability to high permeability layers with severe heterogeneity is not explained.
[0004] Polyacrylamide is a commonly used organic treatment agent in oil fields, usually including nonionic polyacrylamide, partially hydrolyzed polyacrylamide and acrylamide copolymer. The heat and salt resistance of copolymers have been improved, but the production process of such substances is more complicated and the product price is higher. The amide group in the polymer can be hydrolyzed to form carboxyl or carboxylate, which can react with Al-containing 3+ Cr 3+ The metal crosslinking agent undergoes a crosslinking reaction, and the amide group itself can form a three-dimensional gel structure with a phenolic crosslinking agent or a polyethyleneimine crosslinking agent through a covalent bond. The crosslinked polymer gel can improve the temperature and salt resistance of polyacrylamide to a certain extent, but the above crosslinking system has a fast reaction speed at high temperature, resulting in a short gelation time, making it difficult for the gel reaction liquid to reach the deep formation; at the same time, Ca 2+ Mg 2+Ions promote the high-temperature hydrolysis of amide groups and combine with carboxyl groups in an ionic bond, resulting in excessive cross-linking of the gel and dehydration, which reduces the stability of the polymer gel. Prolonging the gelation time and enhancing the strength and stability of the gel under high temperature and high salt conditions are technical problems that need to be solved urgently in oilfield profile control and water plugging.
[0005] In recent years, the research on the construction of organic / inorganic composite gels using cross-linked polyacrylamide and inorganic nanoparticles has attracted increasing attention. The organic and inorganic components enhance the strength and stability of the composite gel through hydrogen bonds, electrostatic interactions or van der Waals forces. Inorganic particles can also be used as cross-linking agents to form physical cross-linking points with polymer molecules. The composite gel has a higher elastic modulus and has become an important research direction for improving crude oil recovery. The inorganic nanoparticles introduced in the preparation of composite gels include: silicon dioxide, aluminum oxide, magnesium oxide, fly ash, montmorillonite, laponite, layered double hydroxides, graphene oxide, graphene, multi-walled carbon nanotubes and carbonate particles.
[0006] The literature [Yifei Liu, Caili Dai, Kai Wang, Chenwei Zou, Mingwei Gao, Yanchao Fang, Mingwei Zhao, Yining Wu, Qing You, Study on a novel cross-linked polymer gel strengthened with silica nanoparticles, Energy Fuels, 2017, 31, 9152-9161] reported a novel cross-linked polymer gel strengthened with silica nanoparticles using hydroquinone and hexamethylenetetramine as crosslinking agents and polyacrylamide as the main agent. 2 Nanoparticles were used to prepare organic / inorganic composite gels. Under the conditions of total mineralization of 37000 mg / L and 110 °C, nano-SiO 2 As the concentration of SiO increases from 0.1wt% to 0.3wt%, the elastic modulus and strength of the composite gel are significantly enhanced. This is due to the 2 There are a large number of hydroxyl groups on the particle surface, which can form hydrogen bonds with amide groups and water molecules and enhance the strength and hydrophilicity of the composite gel. 2 As the particle concentration increases, the gelation time of the composite gel is reduced from 16 hours to 9 hours, which is not conducive to the deep profile control and water plugging operations in the oil field. Patent CN112980412A discloses a profile control agent suitable for high-temperature and high-salt heavy oil reservoirs and its preparation method. The system uses silica sol, silica aluminum sol and aluminum sol as stabilizers to enhance the stability of gel formed by acrylamide / 2-acrylamide-2-methylpropane sulfonic acid, acrylamide / N-vinyl pyrrolidone / 2-acrylamide-2-methylpropane sulfonic acid copolymer and phenolic crosslinking agent. The system can be used in the total mineralization of 22×10 4The composite gel can be gelled under the conditions of 100 mg / L and 130°C and has good long-term stability. However, the gelling time of the composite gel is only 7-15h, and the short gelling time cannot ensure that the system can reach the deep reservoir. Patent CN108587585A uses salt-thickening or temperature-thickening amphiphilic polymers, crosslinking agents, surfactants and inorganic particles (1-50nm) to construct organic / inorganic composite gels and use them as profile control and water plugging agents. When the total mineralization of formation water is 8.5×10 4 Under the conditions of 30 days of aging at 85°C, the dehydration rate is 6.0-7.5%, but the gelation time range shown in the examples is only 3.2-4.5 hours. Short gelation time at high temperature is a common problem of the above composite gels.
[0007] Patent CN102516961A discloses an organic-inorganic composite cross-linking plugging agent suitable for high-temperature oil reservoirs. The system uses polyacrylamide, organic cross-linking agent and water glass to construct a composite gel, which is suitable for 90-140℃ formation profile control and water plugging. It is aged at 130℃ for 90 days without dehydration, but the system needs to use pure water to prepare samples, and does not explain its applicability to high-mineralization formations. Patent CN109679604B and Patent CN111808585A respectively disclose a salt-resistant and high-temperature resistant hydrogel and its preparation method and application, a slow-crosslinking temperature-resistant and salt-resistant high-strength gel and its preparation method and application. They respectively use weak acids (such as acetic acid, etc.) and organic acids (such as chloroacetic acid, etc.) to hydrolyze and generate hydrochloric acid to regulate the cross-linking reaction of polyvinyl alcohol and aldehyde substances, and use nano-silica as a stabilizer to prepare organic / inorganic composite gels, which can be used for 130℃ and formation water with a total mineralization of 22×10 4 mg / L water injection well profile control, but both systems require the use of fresh water to prepare the gel liquid, and their gelling time is 1-2h and 1.5-22h respectively. Although the gelling time of the latter system is extended, there is still a gap compared with the requirements of deep oil field profile control and water plugging construction.
[0008] Patent CN105586024A discloses a plugging agent and a method for high-temperature and high-mineralization oil reservoir profile control and water plugging. The system uses hydrolyzed polyacrylamide as the main agent, phenolic substances as cross-linking agents, sodium carbonate as an inorganic particle inducer, and water containing high concentrations of calcium ions to prepare an organic / inorganic composite gel. The gel formed by the polymer and the cross-linking agent has a certain salt resistance, and the inducer can react with calcium ions to form inorganic particles, which has high temperature resistance. The prepared organic / inorganic composite gel can be used as a plugging agent for 80-120°C and a total mineralization of 8.5×10 4 mg / L, Ca 2+ Concentration 1.2×10 4Under the condition of 100 mg / L, the composite gel was stable at 120°C for 60 days without dehydration, and had high plugging strength and long-term stability. However, the patent did not explain the gelation time of the composite gel and how to control the gelation time. In addition, when sodium carbonate encounters high concentration of calcium ions, it will precipitate quickly in the system and easily form insoluble substances near the wellbore, which is not conducive to the injection of gel liquid and deep profile control and water plugging in the reservoir.
[0009] In summary, compared with inorganic gels and organic gels, the strength and stability of organic / inorganic composite gels are significantly improved, but the obvious shortcoming of this system is the short gelation time under high temperature conditions; in addition, the additional inorganic particles added when preparing composite gels often need to regulate their particle size, layer thickness, concentration, surface properties, etc. Some particles have poor compatibility with high-mineralization formation water or brine. The above factors also limit the application of composite gels. Inorganic salts are an important factor that destroys the stability of polymer gels under high temperature and high salt conditions. Although researchers have tried to use inorganic ions in formation water to prepare organic / inorganic composite gels, there is still a gap in the coordinated regulation of the high-temperature cross-linking reaction time of composite gels, the strength and stability of composite gels, and the comprehensive use of formation mineral resources to prepare organic / inorganic composite gels in situ. Related research is of great significance to the field of chemical profile control and water plugging in oil fields. Summary of the invention:
[0010] In view of the shortcomings of the existing technologies such as the inability to coordinately regulate the gelation time and stability of organic / inorganic composite gels and the in-situ preparation of organic / inorganic composite gels by comprehensive utilization of stratum mineral materials, the patent of the present invention provides a temperature-resistant and salt-resistant organic / inorganic composite gel with urea-delayed cross-linking and a preparation method.
[0011] The specific technical scheme adopted is: the organic / inorganic composite gel is prepared by the following mass percentage composition: polyacrylamide main agent 0.5%-2.0%, phenol cross-linking agent 0.05%-0.80%, aldehyde cross-linking agent 0.05%-0.80%, deoxidizer 0.01%-0.10%, urea 0.20%-5.00%, and the balance is brine.
[0012] The polyacrylamide comprises at least one of nonionic polyacrylamide, partially hydrolyzed polyacrylamide and acrylamide copolymer, preferably nonionic polyacrylamide; the polymer molecular weight is 1 million to 5 million; the phenol cross-linking agent comprises one or more of phenol, resorcinol and hydroquinone, preferably hydroquinone; the aldehyde cross-linking agent comprises formaldehyde or paraformaldehyde; the brine is simulated high-mineralization formation water, wherein the total concentration of calcium and magnesium ions is 2200 to 9000 mg / L, and the total mineralization of the brine is 5.0×10 4 -20.0×10 4 mg / L; in the organic / inorganic composite gel, thiourea is a deoxidizer, which is used to enhance the stability of the composite gel under high temperature conditions.
[0013] At 95-120° C., the urea is not only a retarder for the cross-linking reaction between polyacrylamide and phenolic substances, but also a calcium and magnesium ion precipitant. By delaying the high-temperature cross-linking reaction and regulating the calcium and magnesium ion precipitation reaction, an organic / inorganic composite gel is formed. The gelation time can be regulated within 2.2-26.4 d. The composite gel reaction solution has the characteristics of slow and controllable high-temperature gelation.
[0014] The organic / inorganic composite gel has a temperature of 95-120°C and a total mineralization of 5.0×10 4 -20.0×10 4 The stability time under high temperature and high salt conditions of 2200-9000 mg / L and total calcium and magnesium ion concentration of 2200-9000 mg / L is more than 135 days. The composite gel has good temperature and salt resistance and long stability time.
[0015] The organic / inorganic composite gel can be used as a deep profile control and water plugging agent in high-temperature and high-salinity oil reservoirs.
[0016] The present invention also provides a heat-resistant and salt-resistant organic / inorganic composite gel with urea-delayed crosslinking and a preparation method thereof, comprising the following steps:
[0017] The polymer is added into salt water, mixed and stirred until the polymer is completely dissolved to obtain a polymer salt water solution; a phenolic crosslinking agent, an aldehyde crosslinking agent, a deoxidizer and urea are added into the polymer salt water solution, stirred evenly to obtain a composite gel reaction solution; the composite gel reaction solution is placed at a constant temperature of 95-120° C. for aging to obtain a composite gel.
[0018] The preparation method of the heat-resistant and salt-resistant organic / inorganic composite gel with delayed crosslinking of urea also includes the following control mechanism: urea decomposes under high temperature conditions to produce ammonia and carbon dioxide, and hydroxide and carbonate anions are generated in its aqueous solution, which can delay the crosslinking reaction between polyacrylamide and hydroxymethylphenol according to the nucleophilic substitution mechanism. Under high temperature conditions of 95-120°C, the mass percentage of urea in the reaction system is controlled at 0.20%-5.00%, and the gelation time of the reaction solution can be regulated in the range of 2.2-26.4d. Increasing the urea concentration in the reaction system can effectively prolong the gelation time of the reaction solution, and the control method is simple. The gelation time regulated by this preparation method is significantly longer than the high-temperature gelation time of the composite gel currently reported. This method effectively breaks through the technical bottleneck of fast high-temperature gelation of the composite gel and can better meet the requirements of on-site construction in oil fields.
[0019] The method for preparing the heat-resistant and salt-resistant organic / inorganic composite gel with delayed crosslinking of urea also includes the following reaction mechanism: urea decomposes under high temperature conditions to produce ammonia and carbon dioxide, and hydroxide and carbonate anions are generated in its aqueous solution. Calcium and magnesium ions in the polyacrylamide salt aqueous solution can combine with the above anions to form inorganic particles, and form a heat-resistant and salt-resistant organic / inorganic composite gel in situ with the crosslinked polymer.
[0020] The beneficial effects of the present invention are as follows: the gelation time, gel strength and stability of the composite gel can be coordinated and regulated, and the organic / inorganic composite gel can be prepared in situ by comprehensively utilizing saltwater mineral resources. First, the present invention solves the technical bottleneck problem of the fast gelation speed of polymer gel under high temperature conditions, and utilizes the urea decomposition reaction to delay the nucleophilic substitution cross-linking reaction of polyacrylamide and phenolic substances, that is, the hydroxide and carbonate in the system are utilized to inhibit the protonation of hydroxymethyl and the amide cross-linking reaction. The high-temperature cross-linking reaction time of polyacrylamide can be prolonged by simply controlling the urea concentration of the reaction system, thus creating favorable conditions for the polymer gel to reach the deep oil reservoir; second, the present invention utilizes the urea decomposition reaction to regulate the precipitation reaction of calcium and magnesium ions, and converts the high concentration of calcium and magnesium ions in the formation water into inorganic particles such as carbonates in situ. , and form a high-strength organic / inorganic composite gel in situ with the cross-linked polymer. The prepared composite gel is temperature and salt resistant, which helps to improve the deep profile control and water plugging effect of high-temperature and high-salt oil reservoirs; thirdly, the present invention provides an in-situ preparation method of an organic / inorganic composite gel, which converts high-valent metal ions that destroy the stability of the polymer gel into inorganic particles that enhance the strength and stability of the composite gel, realizes the transformation of unfavorable factors into favorable conditions and the comprehensive utilization of brine mineral resources, uses a wide range of raw materials, has low production costs, and simple operating procedures, and has broad application prospects in the field of deep profile control and water plugging in high-temperature and high-salt oil reservoirs. Description of the drawings:
[0021] The following drawings are provided to illustrate and explain the present invention, but are not intended to limit the scope of the present invention.
[0022] Figure 1 is the XRD pattern of inorganic particles;
[0023] Figure 2 Scanning electron micrographs of the heat-resistant and salt-resistant organic / inorganic composite gel samples with urea-delayed crosslinking, a sample containing salt before washing, b sample containing no salt after washing;
[0024] Figure 3 Figure 2 is the relationship between elastic modulus and oscillation frequency of different gel samples (polymer mass percentage is 1%, reaction temperature is 95°C). Sample symbol explanation: When the mineralization degree (T) in the sample is 0 and the urea concentration (U) is 1.34%, the sample is a fresh water gel, and the label is "fresh water-T0-U1.34"; the mineralization degree (T) in the sample is 15×10 4mg / L, when the urea concentration (U) is 0, the sample is a saline gel, and the label is "Saltwater-T15-U0"; the mineralization degree (T) in the sample is 15×10 4 When the urea concentration (U) is 1.34%, the sample is an organic / inorganic composite gel and is labeled as "Composite-T15-U1.34". The symbols of other organic / inorganic composite gel samples are similar. Specific implementation method:
[0025] The present invention is described in detail below in conjunction with embodiments. It should be pointed out that the embodiments are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by those skilled in the art based on the contents of the present invention still fall within the scope of protection of the present invention.
[0026] In the embodiment, the strength of the gel sample and the corresponding gelation time and stability time are recorded by referring to the GSC (Gel Strength Codes) visual code evaluation method proposed by Sydansk et al. The specific operation is: take 20mL of gel reaction solution (liquid mixture before gelation) and seal it in an ampoule bottle and place it in a constant temperature box for heating. The time when the gel sample reaches the strength code D is taken as the gelation time, and the sample stability time is the time when the gel is dehydrated by 5mL and the dehydration rate (i.e., dehydrated volume / initial volume of gel sample × 100%) reaches 25%. The classification of gel strength grades is shown in Table 1.
[0027] Table 1. Gel strength classification table
[0028]
[0029] The relative molecular weight of the nonionic polyacrylamide used in the examples is 1.4 million, the degree of hydrolysis is 1.3%, and the polymer is provided in the form of a 5% by mass mother liquor. Phenol, resorcinol, hydroquinone, and formaldehyde (37% by mass) are all analytically pure reagents. NaCl, CaCl 2 and MgCl 2 6H 2 O and deionized water to prepare a salt solution, wherein the molar ratio of the metal ions is n Na+ ∶n Ca2+ ∶n Mg2+ =25.52∶1.00∶1.65, the total mineralization of the brine mother liquor is 30×10 4 mg / L. Weigh 127.17g, 9.46g and 28.52g of NaCl and CaCl respectively. 2 and MgCl 2 6H 2O was dissolved in deionized water to prepare 500 mL of brine mother solution with a total mineralization of 30×10 4 mg / L,Na + , Ca 2+ and Mg 2+ The concentrations of 99998.7 mg / L, 6816.0 mg / L and 6818.6 mg / L were respectively. When preparing the gel reaction solution, different proportions of polymer mother liquor, salt mother liquor and deionized water were added according to the designed concentration, and the total mineralization in the sample was adjusted to 5, 10, 15, 20×10 4 mg / L.
[0030] Embodiment 1:
[0031] In a 100 mL beaker, 8 mL of 5% nonionic polyacrylamide mother solution, 6.7 mL of salt mother solution, and 25.3 mL of deionized water were measured and stirred at 500 rpm for 0.5 h to make the sample uniform. The polymer mass percentage was 1% and the mineralization degree was 5×10 4 0.0793 g of hydroquinone and 213 μL of 37% formaldehyde solution were added to the solution under stirring conditions. After the phenolic substances were completely dissolved, 0.0200 g of thiourea and 0.1806 g of urea were added under stirring conditions. The solution was stirred until uniform to obtain the composite gel reaction solution of the present invention. 20 mL of the reaction solution sample was encapsulated in an ampoule bottle and subjected to constant temperature aging to generate a composite gel. The gelling time of the composite gel reaction solution at 95°C was 2.2 days, and the stability time of the composite gel sample exceeded 140.2 days. At the 140.2 day, the sample strength symbol was I.
[0032] Embodiment 2:
[0033] In a 100 mL beaker, 8 mL of 5% nonionic polyacrylamide mother solution, 13.3 mL of salt mother solution, and 18.7 mL of deionized water were measured and stirred at 500 rpm for 0.5 h to make the sample uniform. The polymer mass percentage was 1% and the mineralization degree was 10×10 4 0.0793 g of hydroquinone and 213 μL of 37% formaldehyde solution were added to the solution under stirring conditions. After the phenolic substances were completely dissolved, 0.0200 g of thiourea and 0.3613 g of urea were added under stirring conditions. The solution was stirred until uniform to obtain the composite gel reaction solution of the present invention. 20 mL of the reaction solution sample was encapsulated in an ampoule bottle and subjected to constant temperature aging to generate a composite gel. The gelling time of the composite gel reaction solution at 95°C was 3.6 days, and the stability time of the composite gel sample exceeded 145.7 days. At the 145.7 day, the sample strength symbol was I.
[0034] Embodiment 3:
[0035] In a 100 mL beaker, 8 mL of 5% nonionic polyacrylamide mother solution, 20 mL of salt mother solution, and 12 mL of deionized water were measured and stirred at 500 rpm for 0.5 h to make the sample uniform. The polymer mass percentage was 1% and the mineralization degree was 15×10 4 0.0793 g of hydroquinone and 213 μL of 37% formaldehyde solution were added to the solution under stirring conditions. After the phenolic substances were completely dissolved, 0.0200 g of thiourea and 0.5419 g of urea were added under stirring conditions. The solution was stirred until uniform to obtain the composite gel reaction solution of the present invention. 20 mL of the reaction solution sample was encapsulated in an ampoule bottle and subjected to constant temperature aging to generate a composite gel. The gelling time of the composite gel reaction solution at 95°C was 6.6 days, and the stability time of the composite gel sample exceeded 174.7 days. At the 174.7 day, the sample strength symbol was I.
[0036] Embodiment 4:
[0037] In a 100 mL beaker, 8 mL of 5% nonionic polyacrylamide mother solution, 26.7 mL of salt mother solution, and 5.3 mL of deionized water were measured and stirred at 500 rpm for 0.5 h to make the sample uniform. The polymer mass percentage was 1% and the mineralization degree was 20×10 4 0.0793 g of hydroquinone and 213 μL of 37% formaldehyde solution were added to the solution under stirring conditions. After the phenolic substances were completely dissolved, 0.0200 g of thiourea and 0.7226 g of urea were added under stirring conditions. The solution was stirred until uniform to obtain the composite gel reaction solution of the present invention. 20 mL of the reaction solution sample was encapsulated in an ampoule bottle and subjected to constant temperature aging to generate a composite gel. The gelling time of the composite gel reaction solution at 95°C was 6.8 days, and the stability time of the composite gel sample exceeded 172.1 days. At the 172.1 day, the sample strength symbol was I.
[0038] In Examples 1 to 4, the polymer concentration was fixed at 1%, and the salinity of the brine was regulated to be 5, 10, 15 and 20×10 4 mg / L. The gelation time and stability time can be well regulated by adjusting the urea dosage in the four systems. With the increase of mineralization degree and urea dosage, the gelation time is gradually prolonged, and the stability time of the samples exceeds 140d.
[0039] Comparative Example 1:
[0040] Weigh 0.3796 g CaCl 2 、1.1409g MgCl 2 6H2 O, 0.0200g thiourea, 0.5419g urea, dissolved in deionized water to prepare 40mL inorganic reaction solution, the solution has the same concentration of calcium salt, magnesium salt and urea as the composite gel reaction solution of Example 3 of the present invention. The above solution was sealed in a glass bottle with a lid and aged at 95°C for 30 days to ensure that the inorganic ions therein were fully precipitated, then the glass bottle was taken out, the precipitated sample was fully washed with deionized water to remove the unreacted electrolyte, the obtained precipitate was dried at 95°C, and the sample was subjected to XRD test after grinding. The obtained sample XRD curve is as shown in the attached manual. Figure 1 As shown. By comparing with the standard sample card, it can be confirmed that the inorganic precipitation structure generated in Comparative Example 1 includes calcium carbonate and calcium magnesium carbonate particles. Since the concentrations of calcium, magnesium ions and urea in Comparative Example 1 and Example 3 are the same, the composition of the inorganic particles in the sample of Comparative Example 1 is the same as that in Example 3. This comparative example indirectly confirms the structural characteristics and composition of the inorganic particles in Example 3, that is, the inorganic components contained in Example 3 are calcium carbonate particles and calcium magnesium carbonate particles.
[0041] The sample of Example 3 was first freeze-dried and then observed for morphology. The scanning electron microscope photos are shown in the attached manual. Figure 2 As shown. Figure 2 a It can be seen that the polymer gel has a three-dimensional network structure. Since the solution contains a large amount of sodium chloride, a large number of sodium chloride particles are deposited on the polymer surface or in the pores after the gel dries. It should be pointed out that sodium chloride is dissolved in the solvent when the gel is wet. When the solvent is evaporated, inorganic salts are deposited on the polymer surface. This surface deposition structure is of little significance for enhancing the strength and stability of the gel. In order to specifically observe the distribution of organic and inorganic components, the inventors also washed the composite gel with water to remove the soluble inorganic salts, and then freeze-dried it to observe the morphological characteristics of the complex formed by the insoluble inorganic matter and the organic components. Figure 2 b It can be seen that after the soluble sodium salt and unreacted inorganic salt are washed away from the sample, there are still many particles attached to the surface of the polymer gel. These are insoluble substances formed by calcium and magnesium ions under experimental conditions. The particle diameter is about 200nm. The inorganic particles are embedded in the polymer gel matrix to form a typical organic / inorganic composite structure, which helps to improve the strength and stability of the composite gel.
[0042] Comparative Example 2:
[0043] In a 100 mL beaker, 8 mL of 5% nonionic polyacrylamide mother solution, 20 mL of salt mother solution, and 12 mL of deionized water were measured and stirred at 500 rpm for 0.5 h to make the sample uniform. The polymer mass percentage was 1% and the mineralization degree was 15×10 40.0793g hydroquinone and 213μL formaldehyde solution with a mass percentage of 37% were added to the solution under stirring conditions. After the phenolic substances were completely dissolved, 0.0200g thiourea was added under stirring conditions. The solution was stirred until uniform to obtain a saline gel reaction solution without urea. 20mL of the reaction solution sample was encapsulated in an ampoule bottle and subjected to constant temperature aging to generate saline gel. The gelation time of the saline gel reaction solution at 95°C was 8.2d, and the stability time of the saline gel sample was 35.4d.
[0044] Comparative Example 3:
[0045] In a 100 mL beaker, 8 mL of 5% nonionic polyacrylamide mother solution, 20 mL of salt mother solution, and 12 mL of deionized water were measured and stirred at 500 rpm for 0.5 h to make the sample uniform. The polymer mass percentage was 1% and the mineralization degree was 15×10 4 0.0678g phenol and 213μL formaldehyde solution with a mass percentage of 37% were added to the solution under stirring conditions. After the phenolic substances were completely dissolved, 0.0200g thiourea was added under stirring conditions. The solution was stirred until uniform to obtain a saline gel reaction solution without urea. 20mL of the reaction solution sample was encapsulated in an ampoule bottle and subjected to constant temperature aging to generate saline gel. The gelation time of the saline gel reaction solution at 95°C was 11.3d, and the stability time of the saline gel sample was 35.1d.
[0046] Comparative Example 4:
[0047] In a 100 mL beaker, 8 mL of 5% nonionic polyacrylamide mother solution, 20 mL of salt mother solution, and 12 mL of deionized water were measured and stirred at 500 rpm for 0.5 h to make the sample uniform. The polymer mass percentage was 1% and the mineralization degree was 15×10 4 0.0793g resorcinol and 213μL formaldehyde solution with a mass percentage of 37% were added to the solution under stirring conditions. After the phenolic substances were completely dissolved, 0.0200g thiourea was added under stirring conditions. The solution was stirred until uniform to obtain a saline gel reaction solution without urea. 20mL of the reaction solution sample was encapsulated in an ampoule bottle and subjected to constant temperature aging to generate saline gel. The gelation time of the saline gel at 95°C was 0.6d, and the stability time of the saline gel sample was 49.3d.
[0048] Comparative Examples 2 to 4 are saline gels without urea added to the system. Hydroquinone, phenol, and resorcinol and formaldehyde are used as crosslinking agents to achieve crosslinking reactions with polyacrylamide, among which resorcinol has the shortest gelation time because resorcinol has the highest reactivity. At the same time, the saline gel systems constructed by these three crosslinking agents all have a common defect - the stability time is very short, only 35.1-49.3d, which obviously cannot meet the requirements of oil field production. In contrast, the composite gels of Examples 1 to 4 have the significant advantages of controllable gelation time and long stability time.
[0049] Embodiment 5:
[0050] In a 100 mL beaker, 8 mL of 5% nonionic polyacrylamide mother solution, 20 mL of salt mother solution, and 12 mL of deionized water were measured and stirred at 500 rpm for 0.5 h to make the sample uniform. The polymer mass percentage was 1% and the mineralization degree was 15×10 4 0.0805 g phenol and 213 μL formaldehyde solution with a mass percentage of 37% are added to the solution under stirring conditions. After the phenolic substances are completely dissolved, 0.0200 g thiourea and 0.5419 g urea are added under stirring conditions. The solution is stirred until uniform to obtain the composite gel reaction solution of the present invention. 20 mL of the reaction solution sample is encapsulated in an ampoule bottle and subjected to constant temperature aging to generate a composite gel. The gelling time of the composite gel reaction solution at 95°C is 3.5 days, and the stability time of the composite gel sample exceeds 149.4 days. At the 149.4 day, the sample strength symbol is I.
[0051] Comparative analysis of Example 3 and Example 5 shows that using hydroquinone, phenol and formaldehyde as cross-linking agents and adding urea in different cross-linking systems can prepare composite gels with long gelling time and stable performance, and the preparation method has strong versatility.
[0052] Embodiment 6:
[0053] In a 100 mL beaker, 8 mL of 5% nonionic polyacrylamide mother solution, 20 mL of salt mother solution, and 12 mL of deionized water were measured and stirred at 500 rpm for 0.5 h to make the sample uniform. The polymer mass percentage was 1% and the mineralization degree was 15×10 40.0793 g of hydroquinone and 213 μL of formaldehyde solution with a mass percentage of 37% are added to the solution under stirring conditions. After the phenolic substances are completely dissolved, 0.0200 g of thiourea and 0.8129 g of urea are added under stirring conditions. The solution is stirred until uniform to obtain the composite gel reaction solution of the present invention. 20 mL of the reaction solution sample is encapsulated in an ampoule bottle and subjected to constant temperature aging to generate a composite gel. The gelling time of the composite gel reaction solution at 95°C is 11.0 days, and the stability time of the composite gel sample exceeds 141.9 days. At the 141.9 day, the sample strength symbol is I.
[0054] Embodiment 7:
[0055] In a 100 mL beaker, 8 mL of 5% nonionic polyacrylamide mother solution, 20 mL of salt mother solution, and 12 mL of deionized water were measured and stirred at 500 rpm for 0.5 h to make the sample uniform. The polymer mass percentage was 1% and the mineralization degree was 15×10 4 0.0793 g of hydroquinone and 213 μL of 37% formaldehyde solution were added to the solution under stirring conditions. After the phenolic substances were completely dissolved, 0.0200 g of thiourea and 1.0838 g of urea were added under stirring conditions. The solution was stirred until uniform to obtain the composite gel reaction solution of the present invention. 20 mL of the reaction solution sample was encapsulated in an ampoule bottle and subjected to constant temperature aging to generate a composite gel. The gelling time of the composite gel reaction solution at 95°C was 14.1 days, and the stability time of the composite gel sample exceeded 141.9 days. At 141.9 days, the sample strength symbol was I.
[0056] Embodiment 8:
[0057] In a 100 mL beaker, 8 mL of 5% nonionic polyacrylamide mother solution, 26.7 mL of salt mother solution, and 5.3 mL of deionized water were measured and stirred at 500 rpm for 0.5 h to make the sample uniform. The polymer mass percentage was 1% and the mineralization degree was 20×10 4 0.0793 g of hydroquinone and 213 μL of 37% formaldehyde solution were added to the solution under stirring conditions. After the phenolic substances were completely dissolved, 0.0200 g of thiourea and 1.4451 g of urea were added under stirring conditions. The solution was stirred until uniform to obtain the composite gel reaction solution of the present invention. 20 mL of the reaction solution sample was encapsulated in an ampoule bottle and subjected to constant temperature aging to generate a composite gel. The gelling time of the composite gel reaction solution at 95°C was 26.4 days, and the stability time of the composite gel sample exceeded 135.2 days. At 135.2 days, the sample strength symbol was H.
[0058] Comparative analysis of Example 3, Example 6, Example 7 and Example 8 shows that as the urea concentration in the gel reaction solution increases, the gelation time of the reaction solution gradually prolongs, indicating that urea has a significant regulatory effect on the gelation time of the composite gel. At the same time, the stability time of the organic / inorganic composite gel reaches more than 135 days, which is much longer than the stability time of the salt water gel without urea. The use of urea can coordinately regulate the gelation time and stability time of the gel system, thereby making full use of formation water minerals to prepare organic / inorganic composite gel in situ.
[0059] Embodiment 9:
[0060] In a 100 mL beaker, 8 mL of 5% nonionic polyacrylamide mother solution, 20 mL of salt mother solution, and 12 mL of deionized water were measured and stirred at 500 rpm for 0.5 h to make the sample uniform. The polymer mass percentage was 1% and the mineralization degree was 15×10 4 0.0620 g of hydroquinone and 166 μL of 37% formaldehyde solution were added to the solution under stirring conditions. After the phenolic substances were completely dissolved, 0.0200 g of thiourea and 0.5419 g of urea were added under stirring conditions. The solution was stirred until uniform to obtain the composite gel reaction solution of the present invention. 20 mL of the reaction solution sample was encapsulated in an ampoule bottle and subjected to constant temperature aging to generate a composite gel. The gelling time of the gel reaction solution at 120°C was 2.9 days, and the stability time of the composite gel sample exceeded 141.3 days. At 141.3 days, the sample strength symbol was I.
[0061] Embodiment 10:
[0062] In a 100 mL beaker, 8 mL of 5% nonionic polyacrylamide mother solution, 20 mL of salt mother solution, and 12 mL of deionized water were measured and stirred at 500 rpm for 0.5 h to make the sample uniform. The polymer mass percentage was 1% and the mineralization degree was 15×10 4 0.0620 g of hydroquinone and 166 μL of 37% formaldehyde solution were added to the solution under stirring conditions. After the phenolic substances were completely dissolved, 0.0200 g of thiourea and 0.6774 g of urea were added under stirring conditions. The solution was stirred until uniform to obtain the composite gel reaction solution of the present invention. 20 mL of the reaction solution sample was encapsulated in an ampoule bottle and subjected to constant temperature aging to generate a composite gel. The gelling time of the gel reaction solution at 120°C was 3.5 days, and the stability time of the composite gel sample exceeded 141.3 days. At the 141.3 day, the sample strength symbol was I.
[0063] Comparing Example 3 with Example 9, the gelation time of the composite gel reaction solution at 120°C is shorter than that at 95°C, but the gelation time can still be controlled at 2.9 days; Example 10 further shows that increasing the amount of urea at 120°C can extend the gelation time to 3.5 days, indicating that urea still has a good control ability on the gelation time of the composite gel under high temperature conditions, and the gel stability time exceeds 140 days.
[0064] Instructions attached Figure 3 The elastic modulus-oscillation frequency relationship diagram of gel samples prepared under different mineralization and urea concentration conditions is given, where the polymer mass percentage is 1% and the reaction temperature is 95°C. The experimental results show that the sample with the smallest elastic modulus is the freshwater gel sample - freshwater-T0-U1.34, which is prepared with pure water and the reference mineralization is 15×10 4 The elastic modulus of the system after adding urea to the 100 mg / L gelling solution was the smallest, with a value range of 30-70 Pa. The sample with the second smallest elastic modulus was the sample with a mineralization of 15×10 4 mg / L saline gel sample - saline-T15-U0, the elastic modulus value measured under experimental conditions is 50-67Pa; when the mineralization degree is 5×10 4 -20×10 4 mg / L range, the elastic modulus of the prepared composite gel increases with the increase of solution salinity. 4 The composite gel prepared at 200 mg / L, composite-T5-U0.44, has the smallest elastic modulus, with a value range of 70-85 Pa. The sample with the largest elastic modulus in the composite gel is the one with a mineralization of 20×10 4 The sample prepared at 500 mg / L, composite-T20-U1.79, has a value of 120-157 Pa. The experimental results show that the formation of inorganic particles by urea and high-valent metal ions in salt water is an important reason for improving the strength of composite gel. When there are no high-valent metal ions or urea in the solution, fresh water gel or salt water gel is formed, respectively, and their elastic modulus is small; when the mineralization degree is 5×10 4 -20×10 4 In the mg / L range, the elastic modulus of the composite gel increases with the increase of mineralization, which further illustrates the important contribution of urea and high-valent metal ions to form inorganic particles to enhance the elastic modulus of the composite gel.
Claims
1. A heat-resistant and salt-resistant organic / inorganic composite gel with delayed crosslinking by urea, characterized in that: The method is prepared from the following composition in percentage by mass: 0.50%-2.00% polymer main agent, 0.05%-0.80% phenol cross-linking agent, 0.05%-0.80% aldehyde cross-linking agent, 0.01%-0.10% deoxidizer, 0.20%-5.00% urea, and the balance is salt water; The polymer main agent is polyacrylamide; The phenolic cross-linking agent is at least one of phenol, resorcinol and hydroquinone; The aldehyde cross-linking agent is at least one of formaldehyde and paraformaldehyde; The deoxidizer is thiourea.
2. The organic / inorganic composite gel according to claim 1, characterized in that: The polyacrylamide comprises at least one of nonionic polyacrylamide, partially hydrolyzed polyacrylamide and acrylamide copolymer; The hydrolysis degree of nonionic polyacrylamide does not exceed 4%, the hydrolysis degree of partially hydrolyzed polyacrylamide does not exceed 25%, and the relative molecular weight of the polymer is 1 million to 5 million.
3. The organic / inorganic composite gel according to claim 1, characterized in that: The mineralization degree of the brine is 5.0×10 4 -20.0×10 4 mg / L, the total concentration of calcium and magnesium ions is 2200-9000mg / L.
4. The organic / inorganic composite gel according to claim 1, characterized in that: The organic component in the composite gel is a gel formed by polyacrylamide, phenolic crosslinking agent and aldehyde crosslinking agent, and the inorganic component includes calcium carbonate particles and calcium magnesium carbonate particles. The inorganic particles and the organic components enhance the elastic modulus of the composite gel through coordination.
5. The organic / inorganic composite gel according to claim 1, characterized in that: The gelation time of the composite gel reaction solution can be adjusted between 2.2 and 26.4 days at 95-120°C.
6. The organic / inorganic composite gel according to claim 1, characterized in that: The stability time of the composite gel at 95-120℃ is more than 135d.
7. The organic / inorganic composite gel according to claim 1, characterized in that: The composite gel is suitable for use as a deep profile control and water plugging agent in high-temperature and high-salinity oil reservoirs.
8. The method for preparing the urea-delayed cross-linked heat-resistant and salt-resistant organic / inorganic composite gel according to any one of claims 1 to 7, characterized in that: The following steps are involved: Adding the polymer into the salt water, mixing and stirring until completely dissolved, to obtain a polymer salt water solution; Adding a phenolic crosslinking agent, an aldehyde crosslinking agent, an oxygen scavenger and urea to the polymer salt solution, stirring evenly, to obtain a composite gel reaction solution; The composite gel reaction solution is placed at 95-120° C. for constant temperature aging to obtain a composite gel.
9. The method for preparing the heat-resistant and salt-resistant organic / inorganic composite gel with delayed crosslinking of urea according to claim 8, characterized in that: When the mass percentage of urea in the reaction system is controlled within the range of 0.20%-5.00% at 95-120°C, the gelling time of the reaction solution can be regulated within the range of 2.2-26.4 days. Increasing the urea concentration in the reaction system can prolong the gelling time of the reaction solution.
10. The method for preparing the heat-resistant and salt-resistant organic / inorganic composite gel with delayed crosslinking of urea according to claim 8, characterized in that: The preparation method delays the high-temperature cross-linking reaction of polyacrylamide and realizes the comprehensive utilization of minerals in the brine, converting calcium and magnesium ions that destroy the stability of the polymer gel into calcium carbonate and calcium magnesium carbonate inorganic particles that enhance the strength and stability of the composite gel, thereby realizing the transformation of unfavorable factors into favorable conditions. The method is a method for using a polymer brine solution to in situ prepare an organic / inorganic composite gel with a long gelling time and resistance to temperature and salt.
Citation Information
Patent Citations
Organic / inorganic crosslinking system plugging agent applicable to high-temperature oil reservoir
CN102516961A
Profile-control and water-plugging agent and profile-control and water-plugging method used for profile control and water plugging of high-temperature and high-salinity oil reservoir
CN105586024A
Single-fluid-method inorganic precipitation type plugging agent as well as preparation method and application thereof
CN108003855A
Profile adjusting and water plugging agent and application, profile adjusting and water plugging system and preparation method and application thereof
CN108587585A
A salt- and high-temperature resistant hydrogel, its preparation method and application
CN109679604B
Cited By
Temperature-controlled trigger type nano-composite plugging agent as well as preparation method and application thereof
CN122357109A